2022
DOI: 10.1111/jnu.12811
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐ethnography of developing and living with post‐burn scars

Abstract: Introduction:Post-burn scarring is often cosmetically unappealing and create discomfort. This makes it crucial to understand the experience of individuals living with scars which can offer insights into their recovery. This review sought to develop an in-depth understanding of living with post-burn scars. Design:A systematic review and meta-ethnography approach were employed. We utilized an interpretive approach to inductively generate codes. These codes were examined iteratively using a constant comparison st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(192 reference statements)
0
1
0
Order By: Relevance
“…In most cases, self-immolation causes painful deep burns that eventually lead to death for about 70% of victims (Saadati et al, 2019; Yoosefi Lebni, Abbas, et al, 2020). victims survive, they may experience organ defects and changes in the appearance (Bayuo et al, 2023; Cleary et al, 2021; Yoosefi Lebni et al, 2023). Studies in Iran found that women who survive self-immolation face many problems: Psychological problems, incomplete treatment, lack of supportive social and legal structures, poor self-care, rejection, and social stigma (Mirlashari et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, self-immolation causes painful deep burns that eventually lead to death for about 70% of victims (Saadati et al, 2019; Yoosefi Lebni, Abbas, et al, 2020). victims survive, they may experience organ defects and changes in the appearance (Bayuo et al, 2023; Cleary et al, 2021; Yoosefi Lebni et al, 2023). Studies in Iran found that women who survive self-immolation face many problems: Psychological problems, incomplete treatment, lack of supportive social and legal structures, poor self-care, rejection, and social stigma (Mirlashari et al, 2017).…”
Section: Methodsmentioning
confidence: 99%